Synthesized effects of medium-term exposure to seawater acidification and microplastics on the physiology and energy budget of the thick shell mussel Mytilus coruscus. (1st September 2022) - Sui, Yanming; Zhang, Tao; Yao, Xinyun; Yan, Ming; Yang, Liguo; Mohsen, Mohamed; Nguyen, Haidang; Zhang, Shengmao; Jiang, Hucheng; Lv, Linlan; Zheng, Liang
Abstract: Ocean acidification (OA) and microplastics (MPs) contamination are two results of human excises. In regions like estuarine areas, OA and MPs exposure are happening at the same time. The current research investigated the synthesized effects of OA and MPs exposure for a medium-term duration on the physiology and energy budget of the thick shell mussel Mytilus coruscus . Mussels were treated by six combinations of three MPs levels (0, 10 and 1000 items L −1 ) × two pH levels (7.3, 8.1) for 21 d. As a result, under pH 7.3, clearance rate (CR), food absorption efficiency (AE), respiration rate (RR), and scope for growth (SFG) significantly decreased, while the fecal organic dry weight ratio (E) significantly increased. 1000 items L −1 MPs led to decrease of CR, E, SFG and increase of AE under pH 8.1. Interactive effects from combination of pH and MPs were found in terms of CR, AE, E and RR, but not for SFG of M. coruscus . Graphical abstract: Image 1 Highlights: Ocean acidification (OA) inhibits most energy related physiological indexes in Mytilus coruscus. OA stress impacts the energy budget of mussels. The mussels are tolerant to Microplastics (MPs) by physiological regulation. Interaction of OA and MPs on the mussels are found in terms of some physiological indexes but not scope for growth.